Phytotoxicity and Antimicrobial Activity of Green Synthesized Silver Nanoparticles Using Nigella sativa Seeds on Wheat Seedlings - Ezzat H. Elshazly; Abdel Kareem S. H. Mohamed; Hesham A. Aboelmagd; Gamal A. Gouda; Mohamed H. Abdallah; Emad A. Ewais; Mohammed A. Assiri; Gomaa A. M. Ali (Journal of Chemistry)
Recently, the green synthesis of nanomaterials has grown in popularity and has become one of the most used approaches. Plant extracts are safe for the environment and could be cost-effective for nanoparticle preparation. Silver nanoparticles (AgNPs) have been synthesized using aqueous extracts of Nigella sativa (N. sativa) seeds. The formation of AgNPs was confirmed by using an X-ray diffractometer, a UV-visible spectrometer, and a transmission electron microscope. The phytotoxicity and genotoxicity of different AgNP concentrations (12.5, 25, 50, 75, and 100 μg·L−1) were evaluated by wheat (Triticum aestivum L.) seed germination. The results showed that AgNPs did not significantly affect germination, while root and coleoptile lengths decreased considerably. On the contrary, the biomass of seedlings markedly increased in response to AgNP treatments. Moreover, genotoxicity was detected, especially at high concentrations of AgNPs. DNA, RNA, and total soluble proteins of wheat seedlings significantly decreased. In addition, antimicrobial activities of biosynthesized AgNPs were detected.